Alkyl chain length-regulated in situ intelligent nano-assemblies with AIE-active photosensitizers for photodynamic cancer therapy - Lingyi Shen; Qilong Zhang; Yongchao Yao; Yali Huang; Zhichang Zheng; Ming Li; Hong Xu; Lin Tan; Xukun Liao; Binyi Xia; Lin Li; Carl Redshaw; et al. (Asian Journal of Pharmaceutical Sciences)
Photodynamic therapy (PDT) brings new hope for the treatment of breast cancer due to few side effects and highly effective cell killing; however, the low bioavailability of traditional photosensitizers (PSs) and their dependence on oxygen severely limits their application. Aggregation-induced emission (AIE) PSs can dramatically facilitate the photosensitization effect, which can have positive impacts on tumor PDT. To-date, most AIE PSs lack tumor targeting capability and possess poor cell delivery, resulting in their use in large quantities that are harmful to healthy tissues. In this study, a series of AIE PSs based on pyridinium-substituted triphenylamine salts (TTPAs 1–6) with different alkyl chain lengths are synthesized. Results reveal that TTPAs 1–6 promote the generation of type I and II ROS, including ·OH and 1O2. In particular, the membrane permeability and targeting of TTPAs 4-6 bearing C8-C10 side-chains are higher than TTPAs 1-3 bearing shorter alkyl chains. Additionally, they can assemble with albumin, thereby forming nanoparticles (TTPA 4–6 NPs) in situ in blood, which significantly facilitates mitochondrial-targeting and strong ROS generation ability. Moreover, the TTPA 4–6 NPs are pH-responsive, allowing for increased accumulation or endocytosis of the tumor and enhancing the imaging or therapeutic effect. Therefore, the in vivo distributions of TTPA 4–6 NPs are visually enriched in tumor sites and exhibited excellent PDT efficacy. This work demonstrates a novel strategy for AIE PDT and has the potential to play an essential role in clinical applications using nano-delivery systems.